Overview of Network Slicing: Business and Standards Perspective for Beyond 5G Networks - Khan, Bahram (2021)
The deployment of fifth-generation wireless communications (5G) networks brought a significant difference in the data rate and throughput to the wireless systems. It ensures ultra-low latency and high reliability. In particular, Network Slicing (NS), one of the enablers for the 5G phase-II and beyond, has opened enormous opportunities for the Communications Service Provider (CSPs). NS allows CSPs to create independent virtual networks in the same physical network to guarantee high service levels. This paper provides an overview of the advances in NS from the perspective of the business opportunities and associated standardization activities. Standardization is critical in research as it intends to maintain interoperability among multi-vendor scenarios in telcos. We emphasize highlighting the technical facets of slicing within the business implementation and industry standardization process. Additionally, we address the application of Artificial Intelligence (AI) and Machine Learning (ML) to NS-enabled future networks deployments. A set of use cases and the underlying specific requirements challenges are discussed as well. Finally, future research directions are addressed in detail.